Gewerkschaften im Bundestag: Gemeinwohlorientiert oder Lobbyisten? - Michael Berlemann; Klaus W. Zimmermann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
This article focuses on the role of unionized members of the parliament. Referring to the famous study by Freeman and Medoff (1984) and considering the more recent literature we first review unions' political power at the example of the US. We conclude that trade unions have not been very successful in increasing its monopoly power during the last decades. We then study in how far similar results can be found in Europe, where the degree of unionization is considerably higher than in the US. A recent study by Hönigsberger (2008) for Germany basically concludes union members to overwhelmingly stick to their duties as representatives and thus cannot be seen as the parliamentary arm of the trade unions. However, we present contradicting empirical results, based on a newly constructed dataset for Germany. In a VAR analysis we find that the degree of unionization of parliamentary members has a negative impact on economic growth and at the same time increases inflation while detrended unemployment remains unaffected. The effects are stable even after controlling for partisan politics. Thus, at least in Germany trade unions do not seem to be as weak as they tend to claim.
urn:nbn:de:gbv:705-opus-20927
Keywords: J51; 330; trade unions; unemployment; growth; inflation; Abgeordnete; Gewerkschaftlicher Organisationsgrad; Interessenpolitik; Wirkungsanalyse; Arbeitslosigkeit; Wirtschaftswachstum; Inflation; Deutschland